Risky dietary supplements - Clarkson, P.; Coleman, E.; Rosenbloom, C. (Sports Science Exchange, 2002)
Millions of people rely on dietary supplements for everything from enhancing their sex lives to improving their athletic performances. There is essentially no systematic regulation of the dietary supplement industry, so there is no guarantee that a given supplement will live up to its claims. More important, there is no guarantee that any supplement is safe. We asked a panel of experts to discuss the relative safety of dietary supplements. Each of these experts, Priscilla Clarkson, Ellen Coleman, and Chris Rosenbloom, has authored numerous publications and given many public presentations on various sports nutrition topics - including dietary supplements. Their comments should be carefully weighed by athletes and non-athletes alike who may be considering the use of a dietary supplement. - Which dietary supplements do you think have the most potential for harm? What is the evidence that each of them might be potentially dangerous? - Are there some dietary supplements that are probably safe and effective if consumed according to the manufacturer?s instructions but are likely to be harmful if the consumer ingests substantially more of the product than is recommended? - Do dietary supplements sometimes contain substances not listed on the package that might cause an athlete who used the supplement to fail a drug test for sport competition? - What tips do you have for increasing the confidence of the consumer that a given dietary supplement actually contains the appropriate amounts of the ingredients listed on the package and only those ingredients? - It seems that most dietary supplements have never undergone rigorous scientific testing to determine the efficacy and potential side effects of the supplements. Why is there not more published research on these supplements? - Should the US government regulate dietary supplements? If so, what type of regulation would you like to see? What do you think of the regulations passed by Congress in 1994, i.e., the Dietary Supplement Health and Education Act (DSHEA), which liberalized what manufacturers could claim about their supplements and placed the burden on the FDA to prove that a supplement was harmful?